2012
DOI: 10.1007/s11596-012-0051-5
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of glial activation in rostral ventromedial medulla attenuates mechanical allodynia in a rat model of cancer-induced bone pain

Abstract: Descending nociceptive modulation from the supraspinal structures plays an important role in cancer-induced bone pain (CIBP). Rostral ventromedial medulla (RVM) is a critical component of descending nociceptive facilitation circuitry, but so far the mechanisms are poorly known. In this study, we investigated the role of RVM glial activation in the descending nociceptive facilitation circuitry in a CIBP rat model. CIBP rats showed significant activation of microglia and astrocytes, and also up-regulation of pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…Rat BCP models were established using previously described methods [7,[23][24][25] . In brief, under anesthesia with pentobarbital sodium (40 mg/kg, ip), rats were placed in a supine position, and the right leg was shaved and disinfected with 7% iodine.…”
Section: Bcp Modelingmentioning
confidence: 99%
“…Rat BCP models were established using previously described methods [7,[23][24][25] . In brief, under anesthesia with pentobarbital sodium (40 mg/kg, ip), rats were placed in a supine position, and the right leg was shaved and disinfected with 7% iodine.…”
Section: Bcp Modelingmentioning
confidence: 99%
“…This provides evidence that NGF/TrkA signaling over other neurotrophin subtypes may be more important in cancer pain [46, 65] Recent studies on BDNF have demonstrated a role in the induction and maintenance of behavioral hypersensitivity in a rat model of CIBP by BDNF modulating the NMDA subunit 1 (NR1) at the level of the spinal cord and DRG [99]. Upregulation of BDNF in descending pain modulating areas of the rostral ventromedial medulla (RVM) have been reported in a rat model of CIBP [59] suggesting that BDNF may also play a role in CIBP, yet the clinical evidence of whether anti- NGF or anti-BDNF can attenuate CIBP are unknown.…”
Section: Mechanisms Of Cancer Painmentioning
confidence: 99%
“…Microinjections were performed with a 0.5‐μl Hamilton syringe with a 32‐gauge needle to deliver 0.5 μl of solution (drug or vehicle) slowly over a 5‐min period. Five minutes after completion of the injection, the needle was withdrawn, after which the incision was sutured (Liu et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Controls underwent identical procedures with injection of 0.5 μl 0.2% DMSO in sterile 0.9% NS. Doses employed were those described previously (Wei et al, ; Roberts et al, ; Liu et al, ; Ren et al, ) and from the results of our preliminary experiments. The injection site was subsequently verified histologically (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation